The Role of Effective School Communication in Developing Educational School Administration - Sahbi, Wahiba; Nouadri, Farida (Journal of Human Sciences, 2022)
Successful school administration is considered as the core of the educational and teaching processes, it sets parameters and paths for field’ workers to review the work and follow up the results purposefully, which helps to review the organizations, activities and legislation by amending them and identifying methods of their implementation to achieve the desired goals. This study aimed to identify the crucial importance of having a type of effective communication that is able to manage educational processes within school, ultimately leading to achieve its objectives and goals as well as educational purposes that society seeks. Finally, the study concluded that there must be a need for a modern and conscious educational administration that is able to see the true dimensions of effective communication which facilitates the process of performing essential and basic roles as well as assuming new responsibilities required by modernization process.